Carving Way for Successful Extension of Fodder innovations in mango orchards - Biradar, Nagaratna; Shiva Kumar, B G; Kumar, Vinod (Indian Farming, 2017)
Fodder shortage has become regular phenomena now. The process of cultivation of fodder crops in arable lands hence has begun in the country. This process can be hastened by catalyzing with the appropriate extension methods. Identification of appropriate niches, well designed and implemented capacity development program, making access to propagation material and follow up with the farmers together contributed not only for quick diffusion of fodder technologies but also to keep up the motivation of participating farmers.